Aurelio dictionaries: the analysis of idioms under the perspective of Pedagogical Lexicography - Caldas, Ariane Donizete Delgado Ribeiro [UNESP]; Silva, Odair Luiz Nadin da [UNESP]; Orenha-ottaiano, Adriane [UNESP] (Federal Univ Ceara, 2021)
This article aims to undertake an analysis based on two entries (bread and egg) in three dictionaries of the Aurelio line (Mini Aurelio, Aurelio Junior and Aurelio), in order to verify how Idioms are addressed in each record. The entries presented in this research were selected through a quantitative analysis, which sought to highlight the two most frequent entries from a list of idioms compiled by Seco (2017). From this selection and from the perspective of Pedagogical Lexicography, that says to us that the type of dictionary designed to be used in the teaching of a language, whether mother or foreign, should attend to the needs of the students who use them, we seek to analyze how the selected dictionaries approach the Idioms, in order to check how these expressions are presented to students. This search concludes that, despite the delimitation of the clipping made here, the dictionaries the dictionaries fall short on the pedagogical aspect, as theywe identify the lack of information that is relevant to the consultants. We hope that this research could be deepened in the future, in order to prove the first data found.
Keywords: Pedagogical Lexicography; Idioms; Aurelio Dictionaries